KINERJA PROTOKOL NETWORK REDUNDANSI VRRP, HSRP DAN GLBP PADA LAYANAN VIDEO STREAMING - Krsna Yudha Dharma, I Putu Gede; Sudiarta, Pande Ketut; Setiawan, Widyadi (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUM, 2021)
Nowadays streaming video services have become the main need for internet users. To keep the streaming video service awake, an alternative path is needed to avoid network failure. In creating an alternative path, you can use first hop redundancy protocol (FHRP). In FHRP there are three redundancy protocols including VRRP, HSRP and GLBP. The purpose of this study is to find out better protocol performance, especially by using streaming video services. The method used is to simulate redundancy protocol using GNS-3 software with 3 scenarios that run including normal network, down network and recovery network. As for testing each scenario including testing routers with priority, route trace route, link transfer time and quality of service (QoS) video streaming. Based on the results of the study, it was obtained that GLBP protocol has better performance with an average link transfer time of 1.51 seconds, delay of 8.12 ms, packet loss of 0 % and throughput of 1,248 Mbps. This is because in GLBP protocol there is a load balancing feature that can split the load equally and utilize resources more effectively from each router.